Correction: Impact of physical structure of granular sludge on methanogenesis and methanogenic community structure. Issue 56 (15th October 2019) - Pan, Xiaofang; Wang, Lina; Lv, Nan; Ning, Jing; Zhou, Mingdian; Wang, Tao; Li, Chunxing; Zhu, Gefu
Abstract : Correction for 'Impact of physical structure of granular sludge on methanogenesis and methanogenic community structure' by Xiaofang Pan et al., RSC Adv., 2019, 9, 29570–29578.